2016
DOI: 10.3329/jbau.v13i2.28784
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution load in sediment samples of the Buriganga river in Bangladesh

Abstract: A study was conducted to assess the level of Cr, Pb, Cd, Ni, Zn, Cu, Fe and Mn contamination in the sediment samples of the Buriganga river, at the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh. Total 14 sediment samples were collected from different areas of upstream of the Buriganga river. The mean concentrations of total Cr, Pb, Cd, Ni, Fe, Cu, Zn and Mn in the sediment samples were 173.4, 31.4, 1.5, 153.3, 481.8, 344.2, 12989 and 4036 µg g -1 , respectively. The ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
0
14
3
1
Order By: Relevance
“…A comparison between other local studies (Lake Awasa) [38] and the Awash River Basin indicates that samples from the latter showed higher average concentrations for all tested heavy metals with the exception of Pb. A comparison with reports from other countries exhibited that the concentration of Cd in this study is higher than the mean values in reports from Buriganga River, Bangladesh [39]; Neretva River Valley, Croatia [40]; Yangtze River Basin, China [41]; Lijiang River, China [42]; and Danube River, Germany [43]. However, the Cd concentration from this study is lower than those found in results from Almendares River, Cuba [44] and Tigris River, Turkey [45].…”
Section: Risk Assessmentcontrasting
confidence: 78%
See 1 more Smart Citation
“…A comparison between other local studies (Lake Awasa) [38] and the Awash River Basin indicates that samples from the latter showed higher average concentrations for all tested heavy metals with the exception of Pb. A comparison with reports from other countries exhibited that the concentration of Cd in this study is higher than the mean values in reports from Buriganga River, Bangladesh [39]; Neretva River Valley, Croatia [40]; Yangtze River Basin, China [41]; Lijiang River, China [42]; and Danube River, Germany [43]. However, the Cd concentration from this study is lower than those found in results from Almendares River, Cuba [44] and Tigris River, Turkey [45].…”
Section: Risk Assessmentcontrasting
confidence: 78%
“…Hg and As contents in the Lijiang River, China [42] and the Danube River, Germany [43] were higher than those of the Awash River Basin. Moreover, the mean values for Cr, Cu, Ni, and Zn in Neretva River Valley, Croatia [40]; Yangtze River Basin, China [41]; Lijiang River, China [42]; and Danube River, Germany [43] were lower than the average values of the Awash River Basin while Buriganga River, Baangladish [39]; Almendares River, Cuba [44]; and Tigris River, Turkey [45] showed higher contamination with Cu, Ni, and Zn. Industrial and municipal wastewater are the major artificial sources of Cr, Cu, and Ni [48].…”
Section: Risk Assessmentmentioning
confidence: 85%
“…This study recorded Cr, Cu, Pb and Cd concentrations of Dhaleshwari river water were slightly higher than the findings of Ahmed et al (2012). Concentrations of Cr, Pb, Cd and in river sediment collected from Dhaleshwari river were higher than the findings of Mohiuddin et al (2016) who conducted similar study in Buriganga river. This study reported that the concentrations of Cr, Cu, Pb and Cd in the river sediment were much higher than the findings of Ahmed et al (2012).…”
Section: Heavy Metal Concentrations In Sedimentscontrasting
confidence: 70%
“…During the last few years heavy metal and metalloid load together with organic pollutants of these rivers increased to unexpected levels from various sources; therefore, these rivers are known as the “Biologically Dead Rivers” in Bangladesh [59]. The sediments of the Buriganga River also contain concentrations of Pb, Cd, and Cr higher than the standard values [60,61] (Table 2). The Turag River contains Pb (0.073–0.1mg/L) and Cr (0.039–0.061 mg/L) in higher concentrations because of the heavy industrialization on both sides of this river [55].…”
Section: Water Heavy Metal and Metalloid Pollutionmentioning
confidence: 99%